FORMULATION OF TETRANDRINE BEADS USING IONIC GELATION METHOD CA-PECTINATE COATED PH-SENSITIVE POLYMERS AS COLON-TARGETED DOSAGE FORM - Iswandana, Raditya; Putri, Kurnia Sari Setio; Sandiata, Cindy Espreancelly; Triani, Sisilia; Sari, Santi Purna; Djajadisastra, Joshita (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objectives Pectin, a natural polysaccharide, can be used as colon targeted drug delivery systems. Ionotropic gelation of pectin in the presence of certain divalent cations, such as calcium ions, protects drugs by producing insoluble hydrogels that can be used as a colon-targeted drug delivery carrier. In this study, calcium pectinate beads containing tetrandrine were made and were evaluated for in-vitro drug release and in-vivo study. Methods: Calcium pectinate beads were prepared by ionic gelation method with varied calcium chloride concentration (5%, 10%, and 15%). The best formula was coated with pH sensitive polymers, i.e. Eudragit L100-55, Eudragit L100, HPMCP (Hydroxypropylmethyl Cellulose Phthalate) HP-55 or CAP (Cellulose Acetate Phthalate). Results: Characterization results showed that the beads produced were quite spherical and have yellow-brownish color. After the coating process, beads were used in in-vitro drug release and targeted test. From in-vitro release study, beads coated with Eudragit L100 10% has shown good colon targeted dosage form with percent cumulative release 57.87%. This result also confirmed with the in-vivo test. Beads which were coated by Eudragit L100 10% could be found in the rat intestine. Conclusion: Formula 1 (5% calcium chloride concentration) was chosen as the best beads characterization. Formula 1C (5% beads coated with 10% Eudragit L100) showed an optimal protection from gastric acid in the in-vitro release study and able to deliver the beads to the intestine in the in-vivo targeted test.